LEADERSHIP POTENTIAL AND MOTIVATION ON THE PERFORMANCE OF POLICE PERSONNEL IN TULANG BAWANG - Farhani Kampay, Siti Widriya; Iskandar, Iskandar (Transpublika Publisher, 2024)
The importance of the workforce's role in achieving an institution's goals indicates that the success of the organization heavily depends on the quality and enthusiasm of the involved members. In the context of Tulang Bawang Police Resort, as part of the police institution with a crucial role in maintaining the well-being and social security in the country, the performance of personnel becomes a key factor in achieving these goals. During the initial interviews, concerns about the staff's motivation and enthusiasm at Tulang Bawang Police Resort were discovered. Some employees tend to be lazy and eager to go home, indicating a lack of motivation in carrying out their duties. Awareness of the importance of high motivation and enthusiasm becomes the basis for researchers to conduct further research. This study aims to evaluate the impact of leadership and motivation on the performance of members of the Tulang Bawang Police Resort. This research is quantitative in nature, and the analysis is conducted using the SPSS statistical software. The research sample consists of 30 members of the Tulang Bawang Police Resort. The results indicate that each increase of 1 unit in the leadership scale is followed by a decrease of 2.591 units in performance. Additionally, there is a positive correlation between motivation and performance, where each increase of one unit in motivation is followed by an increase of 0.666 units in performance. It can be concluded that leadership has no influence on performance, while motivation shows a positive and significant impact on performance.